Increasing the church's relevance and impact in poor-resource areas by adding sexual reproductive health to missional activities - Margaret Lynne Docking (Health for All Nations, 2017)
Life saving midwifery knowledge must reach the key influential stakeholders in developing countries if the maternal death rate is to be reduced. The church holds the influence and has the networks and training institutions that can be fully expanded to add sexual reproductive health into their existing studies. This field report documents the author's own sad experiences with maternal deaths in Uganda which has led her toward promoting midwifery knowledge among the church leaders. We have neglected to fully respect culture by avoiding men in our discussions around sex pregnancy birth and family planning. The critical mass of men are our channels to save the mothers, reduce teenage pregnancies, abandoned babies and orphaned children. Christian leaders are the cultural gate keepers and builders of the faith. Our basic training in sexual reproductive health allows men to debate the Bible, their faith, traditional practises and expectations in a safe non-threatening environment. They can then make their own wise decisions about family size. "Without knowledge our people perish." (Hosea 4:6) If we don't urgently add the lifesaving knowledge of family planning and Gods wonderful design of our sexuality for true love union we cannot expect to reduce the maternal deaths and overwhelming poverty. Our command is to teach the whole truth because the truth will set us free. (John 8:32).